The level of public knowledge about the management of burns in the working area of the Puskesmas Kota Timur, Kota Timur Subdistrict, Gorontalo City - Iskandar Simbala; Arifandi Pelealu; Hendra Radjulani (PSPP JOURNALS, 2022)
Burns are injuries caused by touching the surface of the body with an object that produces heat from a heat source or from an intermediary material that can conduct heat, exposure to the sun with high temperatures, electricity, or chemicals, water, etc.) or other substances. which are destructive and loss of tissue by burning the skin (strong acid, strong base), Design and Sample: This study is to analyze the extent of public knowledge about the management of burns in the working area of the Puskesmas Kota Timur, Kota Timur Subdistrict, Gorontalo City. This research method is carried out with a quantitative approach with a descriptive design. The population sample of 100 respondents was taken by non-probability sampling technique. sample area of 6 kelurahan was taken by using Quota sampling technique. Collecting data through observation and analysis of descriptive statistical tests. Results: From the results of the study, it can be seen that there are still many people wrongly using toothpaste for treating burns (73.0%). The results showed that the level of knowledge of the community in the working area of the Puskesmas Kota Timur, Kota Timur Subdistrict, Gorontalo City was included in the sufficient category (56.0%). Discussion and Conclusions: From the researcher's perspective, the community still needs to be given counseling to increase knowledge about handling burns so that people understand what to do and minimize the incidence of burns in the working area of the Tomur City Health Center, Gorontalo City.